Prediksi Kebangkrutan Menggunakan Metode Altman dan Springate pada Perusahaan Penerbangan yang Terdaftar di Bursa Efek Indonesia - Rismadi; Maulivia Riska; Meutia Handayani; Rizki Ramadhan; Cut Yunina Eriva; Talbani Farlian (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to predict bankruptcy in airline companies listed on the Indonesia Stock Exchange, using the Altman and Springate methods during the 2019-2021 period. This research uses quantitative methods in the form of secondary data. The data used is in the form of financial statement data for airline companies listed on the IDX through the website www.idx.com. The population used are airline companies, namely, PT Garuda Indonesia Tbk, PT Air Asia Indonesia Tbk, PT Indonesia Transport & Infrastructure Tbk, and PT Jaya Trishindo Tbk. The results of the Altman and Springate methods can categorize companies as bankrupt or not bankrupt. This study has limited time in collecting research data. Based on calculations using the Altman formula, PT Air Asia did not go bankrupt during the period, PT Indonesia Transport & Infrastructure went bankrupt during the period, while the other two companies had experienced bankruptcy between the 3 periods. Based on the Springate method, the companies PT Garuda Indonesia and PT Indonesia Transport & Infrastructure experienced bankruptcy during the period, PT Air Asia Tbk did not go bankrupt during the period, while PT Jaya Trishindo experienced bankruptcy in the 2020 and 2021 periods. The method is used as a bankruptcy estimate, it cannot be said to be 100% accurate. Bankruptcy can occur with various factors that are not suspected by the company. further researchers can develop research by adding bankruptcy prediction methods and can add observation periods.